A Global Climatology of Explosive Cyclones using a Multi-Tracking Approach. Issue 1 (1st January 2019) - Reale, Marco; Liberato, Margarida L.R.; Lionello, Piero; Pinto, Joaquim G.; Salon, Stefano; Ulbrich, Sven
Abstract: In this study, hemispheric climatologies of explosive cyclones (ECs) derived using a set of different cyclone detection and tracking methods (CDTMs) are analysed. The aim is to evaluate trends and regional characteristics of ECs discussing consensus and disagreement among methods. Areas of both hemispheres characterised by relatively frequent presence of ECs are considered, with particular emphasis on their extremes. Despite the considerable differences (up to 21-38% in the Northern/Southern Hemisphere) in the total number of ECs detected by the various CDTM, this study provides evidence of a good level of agreement among methods concerning spatial distribution of cyclogenesis, track density, their main characteristics (depth, speed, duration, deepening and normalised deepening rate), seasonality and trends. ECs are shown to be deeper, faster and long-lasting with respect to ordinary cyclones in both hemispheres. Southern Hemisphere ECs are typically more intense than those in Northern Hemisphere. On the other hand, ECs in the Northern Hemisphere are characterised by a stronger deepening rate over 6 h and 24 h than in the Southern Hemisphere. Atlantic ECs are usually faster, deeper and characterised by higher deepening and geostrophically adjusted deepening rate than in the Pacific. This is particularly true in the eastern part of the basin. In both basins, ECs in the western side are characterised by higher normalised deepening rates than in the eastern parts. In the Southern Hemisphere, ECs close to Southern Africa and Australia are usually faster, deeper and with higher deepening rates than those close to southern South America. On the other hand, ECs close to southern South America and Southern Africa are characterised by higher normalised deepening rates and duration with respect to ECs close to Australia.